Perlindungan Dan Kepastian Hukum Terhadap Hak Anak Pasca Perceraian - Rury Sagita; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The purpose of marriage is to create a happy family (household) forever, but in reality, many marriages still often end in divorce. Termination of a marriage relationship through a legal process caused by various reasons not only has an impact on the couple involved but will also have a major impact on the children as victims of the divorce. The impact felt by children varies depending on the dynamics between children and parents, as well as what parents do to continue to provide a sense of security and comfort to the children. However, in practice, there are still many violations of children's rights after divorce. The purpose of this study is to determine and analyze why legal certainty for children's rights is difficult to achieve after divorce and what the role of judicial institutions and related parties is in ensuring protection and legal certainty for children after divorce. The research method used is normative juridical with a statutory and conceptual approach. The results of the study show that many parents still do not understand their children's legal rights after divorce, especially regarding custody, support, education, and emotional protection. Although the court has decided on children's rights, its implementation in the field often does not run smoothly.